PENGGUNAAN SUMBER DAYA AIR UNTUK USAHA CUCI MOBIL MY CARWASH DI DENPASAR (Studi Putusan Nomor 770/PID.SUS/2021/PN DPS): The Use of Water Resources for My Carwash Car Wash Business in Denpasar (Study of Decision Number 770/PID.SUS/2021/PN DPS) - Diva Aprilian Fahrezy; Ignatius Pradipa Probandaru (Faculty of Law, Universitas Trisakti, 2025)
Water for business needs activities must have a permit as stipulated in Law 17 of 2017 concerning Water Resources. This research analyzes the Decision of the Denpasar Bali District Court (Number 770/Pid.Sus/2021/PN) regarding the use of water resources without a permit for the My Carwash car wash business activities. The identification problems in this study are how the use of water resources without a license from the government for the My Carwash car wash business in Denpasar is viewed from Law Number 17 of 2019, and what the legal consequences are of the Denpasar District Court Decision 770/Pid.Sus/2021/PN regarding using water resources without a license for the My Carwash car wash business in Denpasar against I Kadek Martha Yoga Prayadnya. This research uses normative legal methods with descriptive research and deductive logic conclusions. Based on the results and conclusion of the study, the use of water resources by I Kadek Martha Yoga Prayadnya is proven to be negligent in not having a water resource exploitation permit in the My Carwash car wash business activities that he owns, then the legal consequences arising from this decision are imposed imprisonment and fines to I Kadek Martha Yoga Prayadnya and revocation of business licenses.